The Problem of Literary and Journalistic Mastery in Uzbek Literary - Shukurova G.H. (Genius Journals, 2022)
The present article covers creativity and analytical skills of one of the brightest representatives of Uzbek literal studies and critics Matyoqub Qo'shjonov. A writer separately studies issues of character, plot, composition and conflict in his works. Main genres of M.Qo'shjonov - review, articles, supervisions, interviews, sketches, essays, previews, letters, monographs among which a main place is given to articles, sketches and essays.
Keywords: Review; Publicity; Character; Plot; Composition; Conflict; Language; Style; Method and skills.